Some recent data on sperm morphology and motility kinetics in Atlantic cod (Gadus morhua L.) - Alavi, Sayyed Mohammad Hadi; Hatef, Azadeh; Butts, Ian A E; Bondarenko, Olga; Cosson, Jacky; Babiak, Igor (Fish physiology and biochemistry, 2021)
Studying biology of sperm provides valuable information to optimize artificial reproduction and is crucial for sustainable aquaculture. Here, we investigated morphology of spermatozoon in Atlantic cod (Gadus morhua) using transmission and scanning electron microscopy. Furthermore, spermatozoa motility kinetics at different osmolalities were studied using computer-assisted sperm analysis software. The spermatozoon lacked an acrosome and consisted of a head, midpiece, and flagellum. The head of spermatozoa was round, oval, and rather elongated in shape, showing high variations in dimensions. There were up to 6 mitochondria that encircled the proximal part of the flagellum. The proximal and distal centrioles were located within the nuclear notch and arranged orthogonal to each other. The axoneme had a typical 9 + 2 microtubule structure. The flagellar length of spermatozoon was 66.94 ± 0.46 μm. Spermatozoa were immotile in the seminal plasma. Dilution of sperm with natural seawater (1100 mOsmol/kg) resulted in initiation of motility for 91.0 ± 3.4% of spermatozoa with average velocity of 86.2 ± 2.3 μm/s and beating frequency of 52 Hz. The duration of spermatozoa motility was > 6 min; however, the percentage of motile spermatozoa decreased at 60 s post-activation. When osmolality of natural seawater was modified using distilled water or NaCl, spermatozoa motility was not initiated at ≤ 400 and ≥ 2500 mOsmol/kg, and the highest percentage of motility was observed at 730-1580 mOsmol/kg. In a sucrose solution, spermatozoa motility was initiated and suppressed at 600 and 1500 mOsmol/kg, respectively, and highest percentage of motility was observed at 800-1100 mOsmol/kg. Spermatozoon morphology comparisons within Gadiformes showed differences in dimensions of head and mitochondria, flagellar length, and number of mitochondria. The present study provides valuable data that can be used for phylogenetic implications based on spermatozoon morphology and for development of artificial fertilization and sperm cryopreservation protocols based on sperm motility.
Keywords: Electron microscopy; osmolární koncentrace; spermie; Osmolality; Sperm velocity; Spermatozoa; Gadus morhua; Male; Animals; Beat frequency; Ions; mužské pohlaví; Osmolar Concentration; Sperm ultrastructure; Sperm Motility; zvířata; motilita spermií